Enigma - RuNyx (Novelist) (Bramble/Tor Publishing Group, 2025)
"Salem Salazar is a Mortimer University legacy and the black sheep of her scandal-ridden, wealthy family. Obsessed with death, she arrives at Mortimer on the hunt for answers about what happened to herperfect, missing older sister. There, she discovers that her sisteris far from the only girl to have gone missing at Mortimer. Salem will do anything to discover what dark forces are killing Mortimer's students... even if it means using herself as bait. And Cazimir vander Waal has caught her scent. He has a dark past, a hidden agenda,and a ravenous appetite for a beautiful, golden-eyed girl who seemsdetermined to risk her life. But he is far from the most dangerous thing at Mortimer."--Provided by publisher.